Prevalence of antimicrobial resistance and integron gene cassettes in Escherichia coli isolated from yaks (Poephagus grunniens) in Aba Tibetan Autonomous Prefecture, China. (October 2017) - Yang, Xin; Zou, Wencheng; Zeng, Jinxin; Xie, Shengze; An, Tianwu; Luo, Xiaolin; Chen, Danyu; Feng, Lan; Cheng, Guangyang; Cai, Run; Huang, Qianru; Wang, Hongning
Abstract: Background: Escherichia coli ( E. coli ) is one of the most relevant opportunistic pathogenic bacteria as it may cause severe morbidity and mortality in yaks ( poephagus grunniens ). In recent years, several kinds of antibiotics have been widely used in Tibetan areas to treat the bacterial diseases, resulting in serious repercussions on the bacterial antibiotic resistance in yaks. This investigation was conducted in order to determine the prevalence of antimicrobial resistance and integron gene cassettes in E. coli isolated from yaks in Aba Tibetan Autonomous Prefecture (Aba TAP), China. Methods: A total of 278 non-duplicated fresh samples were collected from the yaks in Aba TAP for the isolation and identification of E. coli isolates. Antimicrobial susceptibility testing is performed by using the disc diffusion method according to the Clinical and Laboratory Standards Institute guidelines (CLSI, 2013). Various antibiotic resistance genes and integron gene cassettes were detected by polymerase chain reaction (PCR) and sequencing. Results: Overall, a total of 228 E. coli bacteria were isolated from the fresh faeces of yaks in four different geographical regions. 58% of those isolates showed multi-drug resistance capabilities (MDR) in our study. These isolated bacteria showed a high resistance rate to streptomycin (84%), cefotaxime (79%), amikacin (61%) and trimethoprim-sulfamethoxazole (54%). The most common antimicrobial resistance genes in the isolates were bla CTX-M, sul1, aph (3′)-IIa, aac (3)-IIa, aac (6′)-Ib, tetB, with respective detection rates of 65%, 46%, 35%, 13%, 11%, and 10%. Furthermore, 66% and 6% of the strains carried Class 1 and 2 integrons, respectively. However, the class 3 integron was not detected. Gene cassette arrays in the class 1 integron included aadA1, aadA7, aadA5, aadA17, dfrA1, dfrA5, dfrA1-aadA1, dfrA12-aadA2 and dfrA17-aadA5 . The most prevalent gene cassette was aadA1 (20%). For the class 2 integron, dfrA1-sat2-aadA1 (6%) and dfrA1-sat1-aadA1 (0.4%) were also detected as part of this research. Conclusion: High multi-drug resistance rates have been discovered, as well as a prevalence of antibiotic resistance genes and integron gene cassettes in the E. coli isolated from the faeces of yak. This might create a potential problem for treatment of the yaks' bacterial infections as well as food hygiene for humans. It is therefore urgently necessary to begin continuous surveillance and analysis of antibiotic resistance and integron cassettes in other bacteria from yaks. Highlights: It's the first report about integron gene cassettes in E. coli isolates from the faeces of yaks in Aba TAP, China. High multi-drug resistance rates have been discovered in the E. coli isolated from the faeces of yaks. Wide prevalence of antibiotic resistance genes and integron gene cassettes were found in the E. coli .